Compact cross loop resonator based chipless RFID tag with polarization insensitivity. Issue 4 (April 2016) - Sajitha, V. R.; Nijas, C. M.; Roshna, T. K.; Vasudevan, Kesavath; Mohanan, P.
ABSTRACT: A fully printable, passive, compact, and polarization‐independent chipless radio frequency identification (RFID) tag is proposed. A symmetric cross loop resonator is the basic scattering element. The prototype of the tag is fabricated on RT Duroid 5880 substrate with εr = 2.2, tan δ = 0.0008, h = 1 mm. Data is coded in the frequency domain with multiple resonators. A 20‐bit tag of dimensions 4 × 4 cm 2 is demonstrated. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:944–947, 2016